Metastasis of prostate cancer and melanoma cells in a preclinical in vivo mouse model is enhanced by L-plastin expression and phosphorylation - Riplinger, Selina; Wabnitz, Guido H.; Kirchgessner, Henning; Jahraus, Beate; Lasitschka, Felix; Schulte, Bianca; Nakchbandi, Inaam; Samstag, Yvonne (Molecular cancer, 2014)
Tumor cell migration and metastasis require dynamic rearrangements of the actin cytoskeleton. Interestingly, the F-actin cross-linking and stabilizing protein L-plastin, originally described as a leukocyte specific protein, is aberrantly expressed in several non-hematopoietic malignant tumors. Therefore, it has been discussed as a tumor marker. However, systematic in vivo analyses of the functional relevance of L-plastin for tumor cell metastasis were so far lacking.